The History of Children in Australia: An Interdisciplinary Historiography - Pascoe Leahy, Carla (History compass, 2010)
Children have long been shadowy or forgotten figures within historical narratives. It was not until the second half of the twentieth century that a critical historiography of children and childhood emerged. In the Australian context, histories of young people were not published until the 1980s. Whilst the historiography of the child is now a burgeoning field, it has been haunted by two major challenges: a lack of sources authored by children themselves; and a tendency amongst adult scholars to romanticise children. This article situates the Australian historiography of children within an international context. Given the difficulties of reconstructing the lives of children in the past, it argues for an interdisciplinary approach, drawing upon the insights of folklore, material culture, geography and oral history.